Clinical effects and pharmacokinetic variables of romifidine and the peripheral α2‐adrenoceptor antagonist MK‐467 in horses. (November 2016) - de Vries, Annemarie; Pakkanen, Soile AE; Raekallio, Marja R; Ekiri, Abel; Scheinin, Mika; Taylor, Polly M; Vainio, Outi M
Abstract: Objectives: To investigate the effects of MK‐467 on sedation quality, and cardiopulmonary and pharmacokinetic variables in horses sedated intravenously (IV) with romifidine. Study design: Experimental, randomized, crossover design. Animals: Seven healthy mares. Methods: Romifidine (80 μg kg −1 ; R) and MK‐467 (200 μg kg −1 ; MK) were administered IV alone and in combination (R + MK). Levels of sedation and borborygmi were scored. Heart rate (HR), direct arterial blood pressure (ABP) and respiratory rate ( f R ) were recorded. Arterial and venous blood gas analyses were performed and venous plasma drug concentrations were measured. Pharmacokinetic parameters were calculated. Linear mixed modelling for repeated measures, contrasts of least square means by Bonferroni correction tests, one‐wayanova for repeated measures with Bonferroni multiple comparison tests and paired Student's t ‐tests were used to compare results within and between treatments as appropriate. Significance was set at p  < 0.05. Results: After R, ABP increased and HR and f R decreased significantly. After R + MK, HR, f R, systolic and mean ABP decreased. MK alone increased both HR and f R . After R, ABP was significantly higher than after R + MK. HR and f R were significantly higher after MK than after R and R + MK. Areas under the curve for sedation time were similar after R and R + MK. Intestinal activity decreased markedly after R and less after R + MK. Volume of distribution and clearance of romifidine were significantly higher and area under the concentration time curve extrapolated to infinity significantly lower after R + MK than after R. Conclusions: Combined romifidine and MK‐467 prevented the cardiovascular changes commonly seen with romifidine but did not affect sedation quality. Clinical relevance: Combined IV romifidine and MK‐467 can be used to attenuate the cardiovascular effects of romifidine, such as in horses with colic or undergoing general anaesthesia.